Sustainability programs : a design guide to achieving financial, social, and environmental performance - Borges, William (Sustainability professional); Grosskopf, John (John Wiley & Sons, Inc., 2025)
"The triple bottom line (TBL) is a sustainability framework that revolves around the three P's: people, planet and profit. By maximizing all three bottom lines, organizations can achieve a positive impact on the world while enhancing financial performance. The United Nations Brundtland Commission defined sustainability as development that meets the needs of the present without compromising the ability of future generations to meet their own needs. In business, it is about balancing the economic, environmental, and social concerns, with a focus on minimizing or eliminating negative environmental and social impacts while enhancing its financial performance. Integral to sustainability is corporate social responsibility (CSR), which is the business practice of social accountability to itself and its stakeholders through environmental, philanthropic, ethical, and economic responsibility. Leaders, sustainability champions, practitioners, and their supporters, who are interested in creating an SMS, improving an existing one, and/or looking to achieve green certifications will find this book invaluable. Researchers studying sustainability practices and instructors teaching related courses should find this book essential to their endeavors. Students in environmental and business management courses will benefit from its "here's how it's done" approach."-- Provided by publisher.